2007
DOI: 10.1111/j.1365-2249.2007.03534.x
|View full text |Cite
|
Sign up to set email alerts
|

Shift of C3 deposition from localization in the glomerulus into the tubulo-interstitial compartment in the absence of secreted IgM in immune complex glomerulonephritis

Abstract: SummaryThe role of secretory IgM in protecting kidney tissue from immune complex glomerulonephritis induced by 4 mg horse spleen apoferritin and 0·05 mg lipopolysaccharide has been investigated in mutant mice in which B cells do not secrete IgM, but are capable of expressing surface IgM and IgD and secreting other Ig isotypes. Glomerular size, number of glomeruli per crosssection, glomerular cellularity and urine content of protein and creatinine was comparable in treated secreted IgM (sIgM)-deficient and wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…13 Rare case reports have demonstrated predominant or isolated tubulointerstitial lesions with minimal glomerular abnormalities in patients with systemic lupus erythematosus (SLE), 14 suggesting that glomerular and TBM immune complex formation may be separate events with different triggers. 15,16 Yu et al and Hsieh et al have demonstrated tubulointerstitial lesions including inflammation, fibrosis, and atrophy to be significant independent risk factors for renal outcome in lupus nephritis, 17,18 therefore this is an important area for further studies.…”
Section: Discussionmentioning
confidence: 96%
“…13 Rare case reports have demonstrated predominant or isolated tubulointerstitial lesions with minimal glomerular abnormalities in patients with systemic lupus erythematosus (SLE), 14 suggesting that glomerular and TBM immune complex formation may be separate events with different triggers. 15,16 Yu et al and Hsieh et al have demonstrated tubulointerstitial lesions including inflammation, fibrosis, and atrophy to be significant independent risk factors for renal outcome in lupus nephritis, 17,18 therefore this is an important area for further studies.…”
Section: Discussionmentioning
confidence: 96%
“…Most of these studies focused on understanding the role of complement activation on IgM-mediated late apoptotic cell clearance [13], [18], [20], [21], [22], [23], [24], [25]. Other in vivo studies show that IgM can protect immune complex-mediated damage in specific tissues [26], [27]. Notably, similar to secretory IgA, IgM can reach mucosal surfaces independently of other complement proteins by Th17 regulated transcytosis [9], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Our second patient showed a perivascular C3 deposition without vasculitis lesions; peritubular capillary alteration or glomerular deposition, which is a rare case since only 15% showed positive staining [19]. C3 complement component contributes to interstitial injury more than to glomerular lesions, this is due to the fact that Kidney tissue is particularly vulnerable to complementmediated damage due to the low expression of complement regulatory proteins on glomerular and tubular cells [28]. Thus, this deposition argues in favor of an immune-mediated renal diseases and so reinforce the hypothesis of autoimmune origin of TINU syndrome.…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported in identical twins (boys or girls) and two pairs of sisters so far [27][28][29] and two generations of the same family [16] and no reports of geographic clustering of TINU syndrome cases [19,30]. This fact argues against either environmental or genetic factors as dominant influences in the pathogenesis of the disease [19].…”
Section: Discussionmentioning
confidence: 99%